2001
DOI: 10.1042/0264-6021:3590605
|View full text |Cite
|
Sign up to set email alerts
|

Bile-salt hydrophobicity is a key factor regulating rat liver plasma-membrane communication: relation to bilayer structure, fluidity and transporter expression and function

Abstract: Bile-salt hydrophobicity regulates biliary phospholipid secretion and subselection. The aim of this study was to determine whether bile salts can influence liver plasma membrane phospholipids and fluidity in relation to the ATP-dependent transporter. Rats were depleted of bile salts by overnight biliary diversion and then sodium taurocholate was infused intravenously at a constant rate (200 nmol/min per 100 g of body weight), followed by infusion of bile salts with various hydrophobicities (taurochenodeoxychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
(8 reference statements)
1
12
1
Order By: Relevance
“…3B). The change in fluorescence polarization (0.034) was higher than several physiologically significant changes reported in the literature (41)(42)(43). On the contrary to our results with geldanamycin, another N-terminal inhibitor of Hsp90, radicicol (22) did not induce a significant change in DPH fluorescence polarization (data not shown).…”
Section: Geldanamycin Induces An Accelerated Lysis Of Jurkatcontrasting
confidence: 56%
“…3B). The change in fluorescence polarization (0.034) was higher than several physiologically significant changes reported in the literature (41)(42)(43). On the contrary to our results with geldanamycin, another N-terminal inhibitor of Hsp90, radicicol (22) did not induce a significant change in DPH fluorescence polarization (data not shown).…”
Section: Geldanamycin Induces An Accelerated Lysis Of Jurkatcontrasting
confidence: 56%
“…However, it is also observed that the antimicrobial activity depends on the tested microorganisms and can cover the range from no antimicrobial activity up to very strong activity. One reason for this is the different lipid composition of the membrane of the microorganism [8,11,12,15], which strongly influences the membranolytic activity of detergents or peptides.…”
Section: Compartment Concentrationmentioning
confidence: 99%
“…mixed vesicles, mixed micelles, depending on the lipid to detergent ratio, are formed [8,9]. It is described that the microdomains contained in the mixed micelles were able to solubilise cholesterol [10][11][12][13][14]. An important aspect in the formation of mixed micelles lies in the fact that the mixed micelle association lowers the monomeric activity of bile salts and thus prevents the solubilisation and thus destruction and membranolytic effect of the apical membrane of the epithelial cells [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…1 However, high concentrations of lipophilic bile salts have toxic effects. Bile salts alter membrane fluidity 2 and can act pro-or anti-apoptotic. [3][4][5][6] Many liver diseases are aggravated by the cholestatic potential of lipophilic bile salts.…”
mentioning
confidence: 99%